THE RING OF POWER MANIFESTED IN J.R.R. TOLKIEN’S THE LORD OF THE RINGS AND RICHARD WAGNER’S THE RING OF NIBELUNG - PURWATI, HENI (Jurnal Ilmiah Mahasiswa FIB, 2014)
Authors across time and nations may have the similarities in their works. Comparative Study is the field of study which examines the similarities and the dissimilarities between two literary works. However, there are authors who are influenced by another person who is not a writer. For example, English author John Ronald Reuel Tolkien is inspired by a German Composer, Richard Wagner. Thus, the idea of Tolkien’s The Lord of the Rings shares some similarities and dissimilarities with Wagner’s The Ring of Nibelung becomes the problem of this research. The aims of this research are to analyze and interpret how those works share similarities and dissimilarities. This study uses thematic analysis theory because it analyses how the literary works are compared based on their theme. The theme of the two objects is that the one Ring which has the power to rule the world, thus the comparison is based on the Ring of Power. The data of this study is the trilogy The Lord of the Rings novels and the English version script of The Ring of Nibelung operas.This study reveals that there are five similarities and three differences between the “Two Rings of Power”. The similarities are that first, both literary works have similar theme; second, both the Rings are passed many bearers; third, the tales mention about the God’s existence; fourth, is that the Rings are similar in appearance or shape; and the last is that both Rings are evil. On the other hand, the differences between The Lord of the Rings and The Ring of Nibelung are the origin of the Rings of Power, the symbolization of the Gods and the source power of the Rings.The writer suggests that the next studies, especially when they will be focused on the comparison between The Lord of the Rings and The Ring of Nibelung, to trace back their roots of inspiration because they may come from same sources. It is also possible for future researchers to investigate the novels by using other theories, for example the myth theory. The two works can also be approached by using different analysis subject that is the intrinsic aspects in them. Keywords: Ring of Power, comparison, similarity, dissimilarity.